Creation and Preparation of Website Content as a Means of Disseminating Information and Digital Marketing - Winny Perwithosuci; Nur Hidayah; Inda Fresti Puspitasari; Sitti Retno Faridatussalam; Didit Purnomo (Educate: Journal of Community Service in Education, 2024)
The rapid advancements in technology have a beneficial effect. The impact extends beyond the communications sector and also affects the economic sector. An example of a technological advancement is the construction of a website. Websites provide organizations with timely information and facilitate the transition to digital marketing, resulting in cost savings for businesses. Nevertheless, not every corporation or corporate entity has the ability or capacity to effectively utilize this technology. Nasyiatul Aisyiyah (NA) Klaten Regency is currently in need of a website to serve as an information platform and for digital marketing purposes. The objective of this community service initiative is to provide assistance in the creation and compilation of website content for Nasyiatul Aisyiyah (NA) in Klaten Regency. The approach for executing this service activity involves providing training and coaching. The service activities were executed seamlessly and resulted in the creation of a website that serves as an informational platform for Nasyiatul Aisyiyah (NA) Klaten Regency and as a digital marketing tool for the business products of members of the Asosiasi Pengusaha Nasyiatul Aisyiyah (APUNA) Klaten Regency.